THE EFFECT OF CO-BRANDING STRATEGY, BRAND EQUITY ON PURCHASE INTENTION THROUGH BRAND PREFERENCE - Boy - Riznal; Syafrizal - - (Universitas Madura, 2020)
This study aims to determine and analyze the influence of co-branding strategies, brand equity on brand preference purchase intention on Bhumi Tea. This research is a causative study with quantitative methods. This study uses a non-probability sampling technique with a purposive sampling method, the criteria used are consumers who have not consumed Bhumi tea, but have heard about the Bhumi tea in the amount of 200 people by withdrawal using Hair et.al. The results showed that co-branding strategy had a positive and significant effect on brand equity, brand equity had a positive and significant effect on the brand preference, brand preference had a positive and significant effect on purchase intention, and co-branding strategies had a positive and significant effect on purchase intention while the brand equity has a positive and insignificant effect on purchase intention on Bhumi tea.